PEMANFAATAN CITRA SATELIT DAN SISTEM INFORMASI GEOGRAFIS UNTUK PENGEMBANGAN RUANG TERBUKA HIJAU BERDASARKAN ESTIMASI SUHU PERMUKAAN DARATAN DI KOTA PEKALONGAN (Geo-Image, 2016)
Climate changes effect at waterfront city cause increased of sea level, flood and increase of temperature. Increase of temperature has relate with Urban Heat Island phenomena and that is happen at coastal on north of Central Java indicated from 2004 until 2014 has increase of temperature about 0,2530 C. (BMKG Statklim Semarang). Pekalongan City has increase of urban area from 25,61 km2 in 2011 become 25,71 km2 in 2012 (BPS Kota Pekalongan, 2013). The one of solutions to solve the urban heat island phenomena is a green space, but unit of green space in the Pekalongan City about 6,91 km2 or 15,39% from area (BLH Provinsi Jawa Tengah, 2013).The purpose of this research are 1) Understand the condition of green space distribution in Pekalongan City; 2) Understand the distribution of land surrface temperature in Pekalongan City; 3) Understand the priority area of green space development in Pekalongan City. The result of this research indicate the result of land use interpreation from Quickbird satellite imagery has the accurate amount 12,796 Km2 or 27,88% from areawith distribution clustered on the Pekalongan Barat District and Pekalongan SelatanDistrict. Land surface temperature from extraction of Landsat 7 ETM+ satellite imagery in Pekalongan city is 26,870 until 32,090C with correlation between temperature insitu is a 0,66. And the area which become a priority of green space development are BendanSubdistrict, KergonSubdistrict, MedonoSubdistrict, PringlanguSubdistrict in Pekalongan BaratDistrict, KradenanSubdistrict in Pekalongan SelatanSubdistrict, Landungsari Subdistrict and Noyontaan Subdistrict in Pekalongan TimurDistrict with green spaces type like green belt on the road, river and power line buffer zone also yard in the settlement withwide canopy vegetation types.